Implementasi Pendekatan Yuridis Normatif dan Pendekatan Normatif Sosiologis dalam Penelitian Ilmu Hukum - Zulfi Diane Zaini (Law Faculty of Universitas Bandar Lampung, 2011)
This study discussed the implementation of normative legal approach and sociological normative approach in legal science research. Normative legal discipline does not have empirical characteristic in its study, and it studies norms or rules. A complete legal research must be started with an inventory of positive law (normative legal approach). To know how far those positive laws accommodate and fulfill peoples needs, sociological normative approach is also done by using non-law data. The study of faced legal issues can also be added by using historical and comparative legal research approach, so those legal research can find a new legal philosophy. And then, those philosophy or doctrine must be explained in a legal product (law/ regulation) which then, finally all those things will reuse normative legal research approach and thinking.